Recent Teaching and Learning Trends in Health Professional Education - Khan, Mohammad Iqbal (International Journal of Pathology, 2018)
The way medicine is taught and learnt has changedbeyond recognition. Technology of education hasundergone fabulous modification. More emphasis islaid on education which must be competency,contextual and outcome based. The technology had asignificant impact on the practice of teaching, and thisis increasingly becoming evident in the field ofmedicine; where technology‐enabled curriculum ismore and more introduced in unison! Active learningmodalities are adopted rapidly across the globe